Formulasi Zakat Perusahaan Kalla Group di Kota Makassar - Fitrawansah Fitrawansyah; Abdul Wahid Haddade; Aam Azzatil Isma; Sri Aisyah Yope; M. Wahyuddin Abdullah (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2022)
This paper aims to create a zakat formulation based tazkiyah as manifestation of the distribution of sharia value added in Kalla Group companies in Makassar. This paper is a descriptive qualitative research with a phenomenological approach. The research results show that the calculation of zakat for Kalla Group company was carried out at the beginning of the year when the budget meeting was held, the amount of zakat paid by each subsidiary was adjusted to the projected profit target for that year. Kalla Group acknowledges and records zakat as a general expense. After Hadji Kalla Foundation officially became LAZNAS, Kalla Group acknowledged and recorded zakat as a zakat expense that could reduce the company's profits. Another research result formulates the corporate zakat into 2 formulations, 1) Calculation formulation of zakat for companies is based on the total of working capital (current assets-current liabilities) plus net profit after tax, then multiplied by 2.5% to get the amount of zakat to be paid by the company. This formulation is deemed ideal to be implemented on Kalla Group based on the actual conditions of the company which have previously undergone tazkiyah-based screening. 2) This research also produces a reporting formulation in the form of a company’s zakat reporting format which can facilitate companies in classifying related accounts in their corporate zakat calculations. The formulation of the calculation of zakat for companies with tazkiyah screening is hoped to be a manifestation of the distribution of the sharia value added of the company.